Discourse Cohesion and Accessibility of Referents in Oral Narratives: A Comparison of L1 and L2 Acquisition of French and English - Pascale Leclercq; Ewa Lenart (Discours)
Thiss study aims at comparing L1 and L2 acquisition processes through an analysis of the linguistic means used to ensure discourse cohesion in the oral narratives of French and English four-, seven- and ten-year-old children and of adult learners of these two languages. We focused on the use of high accessibility markers (HAM) (zero anaphora, subject and object pronouns) and low accessibility markers (LAM) (definite noun phrases) by the different groups of learners to analyze the way they maintained and switched reference to the protagonists of the story. Our results highlight a tendency to underspecification among children, who use HAM in a higher proportion than native adults and produce ambiguous forms in context; and a tendency to overspecification among adult advanced and intermediate L2 learners, who favour LAM even where pronouns could be envisaged. This might be explained by the impact of cognitive factors as well as crosslinguistic influences on the productions of L1 and L2 learners.